Pengaruh Kapital dan Human Capital Terhadap Produk Domestik Bruto di Indonesia Tahun 1970-2005 - Ratna Setyawati Gunawan; Diah Setyorini Gunawan (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2007)
The article was aimed to analyze the influence of capital and human capital to the gross domestic product (GDP) in Indonesia during 1970-2005. The result, using Engle-Granger’s Error Correction Model, shows that in the short term there is only one variable that have influence to GDP, that is, capital. In the long term estimation, both variables that are capital and human capital have influence to GDP. Key words: capital, human capital, gross domestic product, error correction model